Self-reported and mother-rated personality traits at age 16 are associated with cognitive function measured concurrently and 30 years later. Issue 16 (12th December 2022) - Sutin, Angelina R.; Stephan, Yannick; Luchetti, Martina; Aschwanden, Damaris; Sesker, Amanda A.; O'Súilleabháin, Páraic S.; Terracciano, Antonio
Abstract: Background: Models of personality and health suggest that personality contributes to health outcomes across adulthood. Personality traits, such as neuroticism and conscientiousness, have long-term predictive power for cognitive impairment in older adulthood, a critical health outcome. Less is known about whether personality measured earlier in life is also associated with cognition across adulthood prior to dementia. Methods: Using data from the British Cohort Study 1970 ( N = 4218; 58% female), the current research examined the relation between self-reported and mother-rated personality at age 16 and cognitive function concurrently at age 16 and cognitive function measured 30 years later at age 46, and whether these traits mediate the relation between childhood social class and midlife cognition. Results: Self-reported and mother-rated conscientiousness at age 16 were each associated with every cognitive measure at age 16 and most measures at age 46. Self-reported openness was likewise associated with better cognitive performance on all tasks at age 16 and prospectively predicted age 46 performance (mothers did not rate openness). Mother-rated agreeableness, but not self-reported, was associated with better cognitive performance at both time points. Adolescent personality mediated the relation between childhood social class and midlife cognitive function. Conclusions: The current study advances personality and cognition by showing that (1) adolescent personality predicts midlife cognition 30 years later, (2) both self-reports and mother-ratings are important sources of information on personality associated with midlife cognition, and (3) adolescent personality may be one pathway through which the early life socioeconomic environment is associated with midlife cognition.